If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(9 + -5a) = -23 (9 * -7 + -5a * -7) = -23 (-63 + 35a) = -23 Solving -63 + 35a = -23 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '63' to each side of the equation. -63 + 63 + 35a = -23 + 63 Combine like terms: -63 + 63 = 0 0 + 35a = -23 + 63 35a = -23 + 63 Combine like terms: -23 + 63 = 40 35a = 40 Divide each side by '35'. a = 1.142857143 Simplifying a = 1.142857143
| 3p.9=24 | | -4+3(18-9m)= | | x(x+4)+28=(x-1)(x+8) | | 5=6p-1 | | 2x(3x+x^2)-2x^2=136 | | 5=s-6 | | -(x)whenx=8 | | 63x^2-44x=-5x+60 | | j-20=-23 | | -p+4(3p-2)+5= | | (x*5)+21(1-x)=10 | | 16i+z^2=0 | | 123-95=31y-38y | | 36-4x+8=5+5x-1 | | -3(3x-2)+10x-9= | | 123-95=31y-38 | | B-17=(-38) | | 10-3(10-(8+x))=7x-(x-10) | | F(x)=7x^2-37x+5 | | -258=-7(5n-4)-6 | | cosx*cosx*3-sinx*sinx*3=0 | | 3x-5(x-4)=16 | | 6-8x=3x-9 | | t^2-12t+90=0000 | | -x^2-15x+600=0 | | 3.7x+59.8=33-9.7x | | 0.05x+0.07(9000-x)=510 | | x^2-15x+600=0 | | 36=18s | | (2x+10)(2x-7)=342-4x^2 | | z^2=-16i | | .53+.21t=1.09t-.79 |